IMPLEMENTATION OF PSAK 69 ON SHEEP BIOLOGICAL ASSET AGRICULTURAL PRODUCTS (CASE STUDY AT KUNDORI FARM, BUGEN, SEMARANG) - Setyowati, Ani; Kartika, Shinta Eka; Widayat, Guruh Mulia (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
This research aims to explore how accounting is treated for assets related to the biological activities of livestock businesses. The next aim of this research is to explore the management of sheep's biological assets as an agricultural product in relation to its activities as a cultivation tool for producing agricultural products or as a means of generating income that can be resold for its use. PSAK 69 is a regulation approved by the Financial Accounting Standards Board since 2018. PSAK 69 regulates that biological assets or agricultural products are recognized when they meet several of the same criteria as the asset recognition criteria. Assets are measured at initial recognition and at the end of each financial reporting period at fair value less costs to sell. The research was conducted at the Kundori farm which is located in the Bugen area, Semarang. The research method uses descriptive qualitative methods. The results of research conducted during field observations show that the application of PSAK 69 to the transformation activities of sheep biological assets at Kundori Farm has not been carried out inclusively due to limited knowledge of livestock managers in presenting financial reports in accordance with PSAK 69. In addition, animals are cultivated to produce agricultural products. and sell as additional income.